Analysis of nickel alloys by flame atomic absorption spectrometry Part 3. Method for the determination of chromium (BSI, 1991)
Nickel alloys, Determination of content, Chemical analysis and testing, Chromium, Atomic absorption spectrophotometry, Flame photometry, Spectrophotometry, Precision, Reproducibility, Specimen preparation